Wilson’s Disease. Onset and Complex Diagnosis: Clinical Case - Elena S. Zastelo; Elvira N. Fedulova; Anastasiya N. Gabrikevich; Tatiana V. Skochilova; Anatoly I. Khavkin (Вопросы современной педиатрии)
Background. The low prevalence of Wilson’s disease, diversity of clinical signs, long latent course, inheritance features make it difficult to diagnose and require multidisciplinary approach from doctors. Clinical case description. This article describes a clinical case of Wilson’s disease, rare hereditary multisystem disease, diagnosed in patient F., 13 years old. The disease onset was at the age of 6 masked by gastroesophageal reflux disease. Hepatomegaly, cytolysis, and cholestasis were diagnosed 4 years later, thus diagnosis of hepatitis of unknown origin was established requiring further specification. The decrease of free copper level in serum was revealed at the age of 12, penicillamine test was positive. Molecular genetic testing was performed and the pathogenic variant c.3207C>A (heterozygous state) in the ATP7B gene was revealed. We have measured 4 points via the Leipzig score for Wilson’s disease (Leipzig, 2001): serum ceruloplasmin <20 mg/dL — 1 point, increase in urinary copper excretion of more than 5 times at penicillamine test — 2 points, pathogenic variant c.3207C>A (heterozygous state) in the gene ATP7B — 1 point. This score corresponds to the diagnosis of Wilson’s disease. The use of chelation and hepatoprotective therapy has led to positive dynamics. Thus, the disease can debut with nonspecific, asymptomatic increases in transaminases and ultrasound changes in liver at any age. Wilson’s disease is progressive disease and in the absence of timely initiated therapy, patients die due to complications of cirrhosis and/or (less often) progressive neurological symptoms. The prognosis can be favorable with effective chelation therapy or liver transplantation. Conclusion. The described clinical case demonstrates the variability of clinical signs in children with Wilson’s disease that complicates the diagnostic search and early diagnosis